1999
DOI: 10.1097/00006534-199901000-00026
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pai Syndrome

Abstract: A fourth patient suspected of having Pai syndrome is described. The female baby had a median cleft of the upper lip, a polypoid skin mass in the right nostril, and a conjunctival lipoma in the right eye. A median alveolar cleft was in the oral cavity. The polypoid skin mass was attached to the nasal septum, and a histologic examination disclosed mature adipose tissue with normal skin and no cartilaginous tissue. A computed tomographic scan revealed a lipoma of the corpus callosum. However, the patient was neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…One of the accepted aetiological hypotheses is the persistence of primitive meninges into mature adipose tissue 20 . Patients with CNS lipomas usually present with seizures 5,18 , but those with Pai syndrome or frontonasal dysplasia associated with CNS lipomas do not; this is a constant feature in previous reports [1][2][3]6,[9][10][11][12]14,19 . The authors suggest that isolated CNS lipomas have a different embryological origin compared with those occurring in association with midfacial clefting; this is a 'positive prognostic factor' regarding seizure occurrence and overall clinical behaviour.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…One of the accepted aetiological hypotheses is the persistence of primitive meninges into mature adipose tissue 20 . Patients with CNS lipomas usually present with seizures 5,18 , but those with Pai syndrome or frontonasal dysplasia associated with CNS lipomas do not; this is a constant feature in previous reports [1][2][3]6,[9][10][11][12]14,19 . The authors suggest that isolated CNS lipomas have a different embryological origin compared with those occurring in association with midfacial clefting; this is a 'positive prognostic factor' regarding seizure occurrence and overall clinical behaviour.…”
Section: Discussionmentioning
confidence: 86%
“…Although these lesions have been described in association with various forms of frontonasal dysplasia 16,13 , they seem to be peculiar to Pai syndrome [1][2][3]6,9,11,14,19 . Facial lipomas are benign and are cosmetic issues rather than functional problems.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Mishima et al [10] reported 14 patients with median cleft of the upper lip and polypoid skin masses. Three in addition to their reported patient also had lipoma of the corpus callosum, i.e.…”
Section: Discussionmentioning
confidence: 99%